Investigating the Prolonged Discharge Process in Pediatric Teaching Hospital of Tehran, Iran: A Cross-Sectional Study - Sodabeh Vatankhah; Azam Choopani; Emir Tahmazi Aghdam; Mohammad Esmaeel Tavakoli; Nasrin Joudyian; Hamideh Nafar (Patient Safety and Quality Improvement Journal, 2023)
Introduction:This study aimed to investigate the factors contributing to prolonging the discharge process in a pediatric teaching hospital. Materials and Methods: The present study was a descriptive cross-sectional study carried out on 300 patients discharged from one of the pediatric teaching hospitals in Tehran in 2019. This study was conducted using a mixed method. In the quantitative stage, the statistical form was used, the average discharge time in different hospital wards was measured using the stopwatch method, and the data were analyzed using SPSS V. 25 software and descriptive statistics. A qualitative approach was used, including observations, file reviews, Focus Group Discussion (FGD), and brainstorming with experts from the Quality Improvement Office, ward secretaries, clearance unit experts, pharmacy experts, and ward supervisors, to identify the causes of the prolonged process. Finally, the factors were prioritized and approved using the nominal group method. Results: The average discharge time was 3 hours and 7 minutes; the shortest discharge time belonged to the blood ward, and the longest was to the kidney ward. The causes of delay in discharge were divided into two categories: organizational and human factors. Conclusion:To improvethe the quality of the discharge process and patient satisfaction, solutions such as having assistants write file summaries before the morning round, sending files out of the ward on time, hiring a circular secretary to collect patients' files from various wards, and controlling them using a standard checklist, nurses' training, and continuous supervision were proposed.